Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray pada Pembelajaran PAI dan Budi Pekerti terhadap Keaktifan Peserta Didik di SMP Negeri 4 Batang Anai - Hazmi, Taufiq; Muliati, Indah (Lembaga Yasin AlSys, 2026)
Efforts to enhance students’ active participation in Islamic Religious Education (PAI) and Character Education require the use of effective cooperative learning models, one of which is Two Stay Two Stray (TSTS), whose effectiveness needs to be examined empirically. This study aimed to analyze the significant effect of implementing the TSTS cooperative learning model on students’ activeness in Islamic Religious Education and Character Education at SMP Negeri 4 Batang Anai, focusing on the extent to which the model increases students’ active participation during the learning process. A quantitative approach was employed with a one-group pretest–posttest pre-experimental design. The research population comprised all 27 students of Grade VIII 1 at SMP Negeri 4 Batang Anai, who were simultaneously taken as the sample using a total sampling technique. Data on student activeness were collected using a closed-ended Likert-scale questionnaire consisting of 35 valid items administered at the pre-test and post-test stages. Data were analyzed using descriptive statistics, the Kolmogorov–Smirnov normality test, a homogeneity test, and a paired samples t-test. The results showed a significant increase in student activeness after the implementation of the TSTS model, with the mean activeness score rising from 137.26 in the pre-test to 155.93 in the post-test and a significance value (Sig. 2-tailed) of 0.000 (< 0.05), indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. These findings indicate that the TSTS learning model has a significant effect on increasing students’ activeness in Islamic Religious Education and Character Education, particularly in terms of their ability to collaborate, active listening skills, and willingness to express opinions. The study concludes that the TSTS model is capable of creating a more dynamic, interactive, and enjoyable learning environment, fostering a shift from passive to more active and constructive learning. The implications of this research provide an important contribution for Islamic Religious Education teachers in selecting and implementing cooperative learning strategies to enhance students’ learning activeness.